La plata de Britania : la I novela de Marco Didio Falco - Davis, Lindsey; González Trejo, Horacio, 1937-; Davis, Lindsey (Barcelona, España ; Capital Federal, Buenos Aires, Argentina : Edhasa, 2010)
Marcus Falco, a private detective in ancient Rome, hopes to upgrade his social life when a senator asks him to uncover a plot against his niece. Instead, he finds treachery and conspiracy at the highest levels.
Online resource; title from PDF title page (Digitalia, viewed July 17, 2015)
Keywords: Falco, Marcus Didius, -- 41- -- Fiction; Helena Justina (Fictitious character) -- Fiction; Private investigators -- Rome -- Fiction; Rome -- History -- Vespasian, 69-79 -- Fiction; Great Britain -- History -- To 449 -- Fiction; Detective and mystery fiction; Historical fiction; Electronic books